2003
DOI: 10.1046/j.1365-2141.2003.04643.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential apoptosis and Fas expression on GPI‐negative and GPI‐positive stem cells: a mechanism for the evolution of paroxysmal nocturnal haemoglobinuria*

Abstract: Summary. Paroxysmal nocturnal haemoglobinuria (PNH) has a dual pathogenesis. PIG-A mutations generate clones of haemopoietic stem cells (HSC) lacking glycosylphosphatidylinositol (GPI)-anchored proteins and, secondly, these clones expand because of a selective advantage related to bone marrow failure. The first aspect has been elucidated in detail, but the mechanisms leading to clonal expansion are not well understood. We have previously shown that apoptosis and Fas expression in HSC play a role in bone marrow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
2

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 34 publications
1
8
0
2
Order By: Relevance
“…Both the GPI‐AP − and GPI‐AP + T cells proliferated in response to anti‐CD3 and anti‐CD28 mAbs (Fig. 4B,C), though GPI‐AP − T cells tended to show greater proliferation than GPI‐AP + T cells in keeping with previous reports (29, 30). The addition of HVEM‐IgG inhibited the decline in the CFSE level of GPI‐AP + T cells more potently (27, 31, 32) than that of GPI‐AP − T cells (Fig.…”
Section: Resultssupporting
confidence: 91%
“…Both the GPI‐AP − and GPI‐AP + T cells proliferated in response to anti‐CD3 and anti‐CD28 mAbs (Fig. 4B,C), though GPI‐AP − T cells tended to show greater proliferation than GPI‐AP + T cells in keeping with previous reports (29, 30). The addition of HVEM‐IgG inhibited the decline in the CFSE level of GPI‐AP + T cells more potently (27, 31, 32) than that of GPI‐AP − T cells (Fig.…”
Section: Resultssupporting
confidence: 91%
“…Nevertheless, two of these studies concluded that since the degree of resistance was not proportional to PNH clone size the resistance may be independent of the PIG-A mutation [33,35]. Because primary GPI-AP-deficient CD34 + progenitors exhibited similar proliferative and survival rates to CD34 + progenitors from healthy controls, these studies concluded that the survival advantage of the GPI-AP-deficient cells resulted from diminished survival of GPI-AP + stem cells in a 'hostile' PNH environment [32,34,36]. However, it is possible that GPI-AP-deficient stem cells may also be damaged by the same hostile environment and an intrinsic survival advantage in PNH cells may be obscured when PNH progenitors are compared with normal control cells.…”
Section: Potential Mechanisms Of Clonal Expansion In Pnhmentioning
confidence: 92%
“…35,37 Because primary GPI-AP-deficient CD34 + progenitors exhibited similar proliferative and survival rates to CD34 + progenitors from healthy controls, these studies concluded that the survival advantage of the GPI-AP-deficient cells resulted from diminished survival of GPI-AP + stem cells in a "hostile" PNH environment. 34,36,38 However, it is possible that GPI-AP-deficient stem cells may also be damaged by the same hostile environment, and an intrinsic survival advantage in PNH cells may be obscured when PNH progenitors are compared to normal control cells.…”
Section: Model 1: Pnh Cells Evade Immune Attack Possibly Because a Mmentioning
confidence: 99%